(untitled) (Journal of Legal Studies, 2021)
The author of this paper tackles the concept of intimate conviction of the magistrate (judge, prosecutor) and relevant aspects of the etiology and practical importance of its content, as a subjective basis for establishing judicial questioning tactics that help the magistrate in his/her decision-making. By approaching the process of intimate conviction development as part of an interpersonal communication system, the author analyses the contribution of interpreting nonverbal, extra-semantic clues given by the person being questioned and by all participants in courtroom debates, to the detection of feigned behaviors and the subsequent adjustment of questioning, paving the way for the development of an intimate conviction. Consequently, improving hearing and questioning practices for the accused, the investigated, and witnesses involves professional control and self-control in terms of eye contact, facial expression, gestures, stance, paralanguage, touching, proximity, and dress, in order to masterfully achieve specific goals in delivering justice.